Influence Of Corporate Governance Mechanisms On Financial Statement Fraud With Audit Quality As Moderating Variabel - Rohmawati, Siti Nur Aini; Subekti, Imam (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2026)
Financial statement fraud is a serious issue in the business world that can harm shareholders and other stakeholders. This study aims to examine the influence of corporate governance monitoring mechanisms, specifically board of commissioners’ recommendations and meeting frequency, on financial statement fraud, with audit quality as a moderating variable. The data were obtained from infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. Multiple linear regression analysis using SPSS 26 reveals that both the board of commissioners’ recommendations and the frequency of board meetings have a negative and significant effect on financial statement fraud. However, audit quality does not significantly moderate the relationship between those governance mechanisms and fraud. These findings contribute to the corporate governance and auditing literature by emphasizing the importance of effective internal monitoring.